Socialization as a factor of influence on the satisfaction of participants of the Fruška gora mountaineering marathon - Marković Jelica; Zubanov Violeta; Đere Lukrecija (University Educons, Faculty of Sports and Tourism, Novi Sad, 2015)
Customer satisfaction is a guarantee of success in all fields, including those related to the organization of sport events. As a consequence of the event quality appears visitor satisfaction which significantly impacts on the their loyalty and 'word of mouth' promotion, so examination of these categories is especially important to the event organizers in order to control and improve the event. Sports events can be viewed in a broader context, where it is not of primary importance reaching the sports results, but is more emphasized its non-competitive nature. In this case, the sport events include recreation, relaxation, entertainment and leisure, with a significantly different approach and intentions of the organization. Such events lead to intercultural exchange, increase the level of socialization and promote physical activity as a function of improving health. Having in mind that it assumed the characteristics of mass and has become an influential factor in the Vojvodina tourism, this study aims to analyze the quality of the Mountaineering marathon on Fruška gora from the perspective of the participants' satisfaction. For collecting the data, it was used the questionnaire. The sample included 134 participants of the 35th Mountaineering marathon on Fruška gora. For measuring this event quality, it was used modified model SEQSS with 4 dimensions: quality of marathon program, quality of interaction, quality of outcomes and quality of the physical environment. The results have shown that the quality of all measured dimensions is at a high level and that measuring dimension the quality outcome, which includes the socialization and valence, has the greatest impact on the satisfaction of the participants.